Criminal Justice System Law Elimination of Domestic Violence: Case Study at Polda Jateng - Nur Faidah (Program Studi DIII Rekam Medis dan Informasi Kesehatan, 2022)
The problems that will be studied are: 1) How is the criminalization system in the law on the elimination of domestic violence, 2) What are the obstacles faced in punishing perpetrators of domestic violence. This research will be compiled using a normative legal research type, namely a process to find a legal rule, legal principles, and legal doctrines in order to answer the legal issues faced. The results of the study concluded that: (1). The regulation of the criminalization system in the Criminal Code with Law Number 23 of 2004 concerning the Elimination of Domestic Violence is the same, namely recognizing the imposition of imprisonment and fines, only the length of the prison sentence and the amount of the fine are not the same. Related to the legal subject and the regulatory system both in the Criminal Code and in Law Number 23 of 2004 concerning the Elimination of Domestic Violence are the same, namely using the legal subject of people and a single track system. (2). The obstacles faced in punishing perpetrators of domestic violence are: The legal factor itself, the factor of law enforcement officers, the factor of facilities and facilities.